Privacy and Private Law: The Dilemma of Justification - Austin, Lisa (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
In recent years there has been a remarkable convergence across several common law jurisdictions regarding the need to recognize some form of a tort of invasion of privacy, particularly with respect to the publication of private facts. Despite this convergence, the author argues that there remains a palpable “containment anxiety” at play in the jurisprudence that is responsible for a number of recurring tensions regarding the scope of protection.Instead of focusing on the question of how to define privacy, this paper frames the containment anxiety at issue in the cases in terms of a justificatory dilemma rather than a definitional one. Using the work of Mill and Kant, the author argues that if we understand privacy rights as protecting either the value of autonomy or freedom from harm then we can justify a narrow legal right to privacy. Although this can explain the containment anxiety in the jurisprudence, it severely undermines the growing recognition of the importance of privacy. Therefore this paper proposes an alternative justification for privacy rights that is rooted in the value of protecting identity interests, where identity is understood in terms of one's capacity for self-presentation.